Experimental Study on Microstructure Evolution and Fractal Features of Expansive Soil Improved by MICP Method - Su, Huanyu; Xiao, Hongbin; Li, Zhenyu; Tian, Xuwen; Luo, Shenping; Yu, Xinpei; Ouyang, Qianwen (Frontiers in Materials, 2022)
Experimental study on one-dimensional consolidation and scanning electron microscope imaging of expansive soil improved by MICP method has been carried out, by using WG type consolidator and electron scanning microscope. Theoretical analysis on microstructure evolution process of improved expansive soil has been carried out based on fractal theory and damage theory. Through the research, the influence mechanism of cementation and filling effect of calcium carbonate precipitation on the microstructure of improved soil samples such as particle size and pore characteristics is revealed. Based on fractal theory , a porosity calculation model of improved expansive soil has been established considering microstructure damage of soil. Furthermore, a fractal calculation theory of consolidation deformation of improved expansive soil has been proposed.The relevant calculation parameters have also been determined. The rationality of this calculation theory is verified by comparing the calculated results with the tested results. With these research results, a theoretical foundation for further research on microstructure evolution of expansive soil improved by MICP method has been laid. A new train of thought for quantitative research on the water stability and swell–shrink characteristics as well as strength characteristics of improved expansive soil has been provided.